2016
DOI: 10.1002/cnm.2811
|View full text |Cite
|
Sign up to set email alerts
|

Vessel segmentation from abdominal magnetic resonance images: adaptive and reconstructive approach

Abstract: The liver vessels, which have low signal and run next to brighter bile ducts, are difficult to segment from MR images. This study presents a fully automated and adaptive method to segment portal and hepatic veins on magnetic resonance images. In the proposed approach, segmentation of these vessels is achieved in four stages: (i) initial segmentation, (ii) refinement, (iii) reconstruction, and (iv) post-processing. In the initial segmentation stage, k-means clustering is used, the results of which are refined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…In [23], k-means clustering is used for rough liver vessel segmentation. Further iterative refinement steps based on morphological operations are applied to refine the segmentation.…”
Section: A Unsupervisedmentioning
confidence: 99%
See 1 more Smart Citation
“…In [23], k-means clustering is used for rough liver vessel segmentation. Further iterative refinement steps based on morphological operations are applied to refine the segmentation.…”
Section: A Unsupervisedmentioning
confidence: 99%
“…Feng et al [20] 2010 Brain MRA Unsupervised machine learning Hassouna et al [21] 2006 Brain MRA (Sec. V-A) Oliveira et al [22] 2011 Liver CT Goceri et al [23] 2017 Liver MRI Bruyninckx et al [24] 2010 Liver CT Bruyninckx et al [25] 2009 Lung CT Asad et al [26] 2017 Retina CFP Mapayi et al [27] 2015 Retina CFP Sreejini et al [28] 2015 Retina CFP Cinsdikici et al [29] 2009 Retina CFP Al-Rawi et al [30] 2007 Retina CFP Hanaoka et al [31] 2015 Brain MRA Supervised machine learning Sironi et al [32] 2014 Brain Microscopy (Sec. V-B) Merkow et al [33] 2016 Cardiovascular and Lung CT and MRI Sankaran et al [34] 2016 Coronary CTA Schaap et al [35] 2011 Coronary CTA Zheng et al [36] 2011 Coronary CT Nekovei et al [37] 1995 Coronary CT Smistad et al [38] 2016 Femoral region, Carotid US Chu et al [39] 2016 Liver X-ray fluoroscopic Orlando et al [40] 2017 Retina CFP Dasgupta et al [41] 2017 Retina CFP Mo et al [42] 2017 Retina CFP Lahiri et al [43] 2017 Retina CFP Annunziata et al [44] 2016 Retina Microscopy Fu et al [45] 2016 Retina CFP Luo et al [46] 2016 Retina CFP Liskowski et al [47] 2016 Retina CFP Li et al [48] 2016 Retina CFP Javidi et al [49] 2016 Retina CFP Maninis et al [50] 2016 Retina CFP Prentasvic et al [51] 2016 Retina CT Wu et al [52] 2016 Retina CFP Annunziata et al [53] 2015 Retina Microscopy Annunziata et al [54] 2015 Retina Microscopy Vega et al [55] 2015 Retina CFP Wang et al …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Bruyninckx et al [28] segmented the whole portal vein including peripheral branches and obtained Dice coefficient from 0.53 to 0.68. Recently, Goceri et al [31] reported Dice coefficient from 0.51 to 0.62 for segmentation of portal vein from MR images. The previous work emphasized that PV segmentation is compromised by image noise and the presence of hepatic arteries and other veins.…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised classifiers are based on the statistical properties of the input data of specific image features. Examples include principal component analysis, K‐means clustering, and Fuzzy C‐means clustering …”
Section: Image Processingmentioning
confidence: 99%